2006
DOI: 10.1097/01.sla.0000206419.65678.2e
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Reconstruction in Right Lobe Living-Donor Liver Transplantation

Abstract: The authors found an increase in the biliary stricture rate in the duct-to-duct choledochocholedochostomy group. Because of greater physiologic bilioenteric continuity, less incidence of leakage, and easy endoscopic access, duct-to-duct reconstruction represents a feasible technique in right lobe LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
219
6
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(233 citation statements)
references
References 36 publications
5
219
6
3
Order By: Relevance
“…Although the Kyoto group reported that they recently started to use 7-0 monofilament suture, they did not report the outcomes of using this material. 2 Recently, Yan et al 15 reported the favorable results of a microsurgical technique for biliary reconstruction of small hepatic ducts with 8-0 Prolene. In the future, further study with larger numbers of patients using smaller suture materials for the biliary anastomosis should be initiated to determine the effective method to reduce the incidence of biliary complications.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Kyoto group reported that they recently started to use 7-0 monofilament suture, they did not report the outcomes of using this material. 2 Recently, Yan et al 15 reported the favorable results of a microsurgical technique for biliary reconstruction of small hepatic ducts with 8-0 Prolene. In the future, further study with larger numbers of patients using smaller suture materials for the biliary anastomosis should be initiated to determine the effective method to reduce the incidence of biliary complications.…”
Section: Figmentioning
confidence: 99%
“…Incidences of up to 40% have been reported for long-term biliary complications among duct-to-duct biliary reconstructions in right or left lobe LDLT. [1][2][3][4] Biliary stricture and leakage at the anastomotic site are major concerns since they are strongly associated with surgical techniques of bile duct preparation and anastomosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with advanced liver disease before transplantation seem to be more likely to develop ITBL compared to lower Child and Pugh-stages [1]. Deteriorated preoperative status, early biliary complications and "small-for-size" transplantation are currently suspected to contribute to the occurrence and progression of ITBL [55]. Further potential confounders regarding the recipient (age, gender) do not seem to play a significant role in the pathogenesis of ITBL [1].…”
Section: Epidemiologic Aspectsmentioning
confidence: 99%
“…Bacterial ascension leading to cholangitis may negate the expected advantage of reduced cold ischemia time [55,57]. Thus, the main advantages of choledocho-choledochostomy comprise the integrity of anatomic barrier regarding the reflux of intestinal flora to a great extent, better technical feasibility than Roux-en-Y and physiological condition for an endoscopic access [35,58].…”
Section: Reconstructive Techniquementioning
confidence: 99%